Traditionalism in Brazil: Sufism, Ta'i Chi, and Olavo de Carvalho - Sedgwick, Mark (Aries, 2021)
The Traditionalist movement that derives from the French esoteric philosopher René Guénon is known to have been influential in Europe and North America, especially through the activities of religious groups, usually of Sufi origin, and also through the growing impact of the political version of Traditionalism first developed by the Italian esoteric philosopher Julius Evola. This article looks at Traditionalism beyond Europe and North America, taking the important case of Brazil during the 1980s and 1990s, where one of the main Traditionalist Sufi groups, the US -based Maryamiyya, became established, and where two local groups developed, one of which focused exclusively on doctrine, and one of which turned not to Sufism but to T’ai chi and Brazilian indigenous religion. The article also considers a new and important political philosopher, Olavo de Carvalho, who emerged from the Brazilian Traditionalist milieu. Carvalho applied Guénon to political issues rather as Evola had, but unlike Evola combined Traditionalism with Roman Catholicism, a development also found in Argentina during the early twentieth century. During the 2010s, Carvalho’s radical rightist philosophy became widely known in Brazil, where his admirers included the president, Jair Bolsonaro.